Crystallographic Preferred Orientation (CPO) Development Governs Strain Weakening in Ice: Insights From High‐Temperature Deformation Experiments. Issue 12 (15th December 2021) - Fan, Sheng; Cross, Andrew J.; Prior, David J.; Goldsby, David L.; Hager, Travis F.; Negrini, Marianne; Qi, Chao
Abstract: Strain weakening leads to the formation of high‐strain shear zones and strongly influences terrestrial ice discharge. In glacial flow models, strain weakening is assumed to arise from the alignment of weak basal planes—the development of a crystallographic preferred orientation, CPO—during flow. However, in experiments, ice strain weakening also coincides with grain size reduction, which has been invoked as a weakening mechanism in other minerals. To interrogate the relative contributions of CPO development and grain size reduction toward ice strain weakening, we deformed initially isotropic polycrystalline ice samples to progressively higher strains between −4 and −30°C. Microstructural measurements were subsequently combined with flow laws to separately model the mechanical response expected to arise from CPO development and grain size reduction. Magnitudes of strain weakening predicted by the constitutive flow laws were then compared with the experimental measurements. Flow laws that only consider grain size do not predict weakening with strain despite grain size reduction. In contrast, flow laws solely considering CPO effects can reproduce the measured strain weakening. Thus, it is reasonable to assume that strain weakening in ice is dominated by CPO development, at least under high temperature ( T h ${T}_{h}$  ≥ 0.9) and high stress (>1 MPa), like those in our experiments. We speculate that at high homologous temperatures ( T h ${T}_{h}$ ≥ 0.9), CPO development will also govern the strain weakening behavior of other viscously anisotropic minerals, like olivine and quartz. Overall, we emphasize that geodynamic and glaciological models should incorporate CPOs to account for strain weakening, especially at high homologous temperatures. Plain Language Summary: At high temperatures, ice and other minerals become mechanically weaker during deformation. This "strain weakening" behavior is thought to arise from microscopic processes that reduce grain sizes and align weak lattice planes. Strain weakening is important because it influences the continent‐scale flow of rocks and minerals, including terrestrial ice flow. To quantify the relative contributions of grain size reduction and crystal alignment to strain weakening, we deformed ice samples by varying amounts. The microstructure of each sample was then examined using an electron microscope to measure grain size and crystal alignment. These microstructural data were used to predict the strength of each sample using previously published equations ("flow laws") that link microstructure to sample strength. Model predictions were compared to the measured strength of each sample. We found that very little weakening is predicted due to grain size effects, whereas almost all the observed strain weakening can be accounted for by crystal alignment. Our new results demonstrate that at temperatures approaching a mineral's melting point—like in polar ice sheets and glaciers—strain weakening is governed by the progressive alignment of weak crystal lattice planes. Models of rock and ice flow should therefore account for both grain size and crystal alignment effects. Key Points: Contributions of grain size reduction and CPO development to strain weakening in ice are quantified using experimental data Strain weakening can be accounted for entirely using constitutive flow laws that account for CPO development; grain size plays a negligible role Glaciological and geodynamic models need to account for CPO development in viscously anisotropic minerals like ice, olivine, and quartz